Strategic Planning Monitoring System (SPMS) / Abg Hamizam Abang Mohar … [et al.] - Abang Mohar, Abg Hamizam; Bujang Khedif, Lenny Yusrina; Narawi, Azlina; Abdollah, Ida izumi; Putit, Sulastri; Mohd Jawi, Abdul Ismail (Division of Research and Industry Linkages, 2017)
Strategic plans, all too often they don't work and one of the reason Is there is lack of follow through after initial planning that is there is poor tracking of progress. Under such pretext, Strategic Planning Monitoring System (SPMS) is to address the issue. SPMS is the online based system and its primary objective is to assist managers to monitor the progress against target, simultaneously the performance of respective departments/units, as well as the contributions towards the strategic planning long term objectives. SPMS is a systematic and organized approach in managing organization’s strategic planning database. SPMS procedures are relatively straightforward, where the inputs are the planning period, strategic objectives, departments/units, strategies adopted and performance indicators. These are managed by the system administrator and process owners. SPMS are updated online, periodically. The progresses are directly managed by the respective department/units online from their respective terminals. Its immediate access by the process owners allows the progress to be updated at anytime. SPMS outputs are presented in the form of standard report as well as charts based on the requirement of the users, and are also made available to top management for holistic viewing. This reports form the basis for realistic management decision makings. The features of SPMS which support easy access and updating would facilitate timely progress reports that are critical for immediate corrective action (if necessary). This enhances communications between 'participants' as well as a move towards paperless environments. SPMS has potentials to be further developed, through the features of charts and linking it with organizations applications and database for more effective control over its resources and performance that will assist managements at all level in their decision makings.